Efficacy of Arsenical Herbicides and their Doses on the Control of Aristida Species - Bondale, K. V.; Daulay, H. S. (Indian Forester, 1969)
Aristida species are among the notorious grasses which appear at the last stage of deterioration of grassland flora. Their fruits bearing sharp callus and irritating owns are troublesome to grazing animals. Their elimination is also necessary for increasing the quality and productivity of grasslands. Ansar 529, an arsenical selective herbicide has been found to be very efficient than Phytar 560. 72 percent of the weed population could be killed by spraying it at the rate of 1.0 kg active ingredient in 500 litres of water per hectare. Compared with untreated plants the herbicidal dose tended to reduce the plant moisture content to the extent of 45 percent within eight days of spray.